Heterojunction impedes ion induced metallization in 2D transition metal dichalcogenides - Raheel Hammad; Shuvadip Pradhan; Amar Kumar; Tharangattu N. Narayanan; Soumya Ghosh (npj 2D Materials and Applications)
Abstract Layered semiconductor materials such as transition metal dichalcogenides are known to undergo phase transition from the semiconducting (H) to a metallic/quasi-metallic ( $${\rm{T}}/{{\rm{T}}}^{{′} }$$ T / T ′ ) phase upon ion intercalation, thus changing their physical and electronic properties. Initially, based on a computational set-up that treats both phases (H and T’) on the same footing and allows extraction of electron density from lithium intercalated MoS2, we predict that the phase transition can be delayed in MoS2 with almost 1.5 times the amount of cation accommodation while the layers are in contact with another material (MoO3), forming a type-II heterostructure. This important theoretical prediction is then validated via in situ Raman spectroscopy and electron transport measurements, where the concentration of the intercalated Li-ions is controlled by applying an external voltage. The ability to store more Li-ions in the same phase extends the scope of these heterostructures in light driven processes/devices, e.g. photocatalysis, and light-chargeable batteries.